Free-volume correlations in positron-sensitive annihilation modes in chalcogenide vitreous semiconductors: on the path from illusions towards realistic physical description - Shpotyuk, O.I.; Vakiv, M.M.; Shpotyuk, M.V.; Ingram, A.; Filipecki, J.; Vaskiv, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
A newly modified correlation equation between defect-related positron lifetime t₂ (ns) defined within two-state model and corresponding radius R (Å) of freevolume positron traps in the full non-linear form or simplified linear-approximated is proved to account for compositional trends in void volume evolution of chalcogenide semiconductor compounds like binary As-S(Se) glasses. Specific chemical environment of free-volume voids associated with neighbouring network-forming polyhedrons is shown to play a decisive role in this correlation, leading to systematically enhanced estimated void sizes in comparison with typical molecular substrates, such as polymers.